2018
DOI: 10.1007/s10236-018-1162-8
|View full text |Cite
|
Sign up to set email alerts
|

The influence of groundwater depth on coastal dune development at sand flats close to inlets

Abstract: A cellular automata model is used to analyze the effects of groundwater levels and sediment supply on aeolian dune development occurring on sand flats close to inlets. The model considers, in a schematized and probabilistic way, aeolian transport processes, groundwater influence, vegetation development, and combined effects of waves and tides that can both erode and accrete the sand flat. Next to three idealized cases, a sand flat adjoining the barrier island of Texel, the Netherlands, was chosen as a case stu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
35
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
1

Relationship

4
4

Authors

Journals

citations
Cited by 22 publications
(35 citation statements)
references
References 35 publications
(54 reference statements)
0
35
0
Order By: Relevance
“…Yes 84 422 No 93 524 Table 6 shows that even though during onshore wind conditions with wind speeds above 7 m/s, still 55% of the time transport was not observed. This can be related to water level variation which influences the groundwater level and therefore, the moisture content of the surface [52][53][54][55]. Figure 16 presents the cumulative distribution of water levels and wind speeds for the cases presented in Table 6.…”
Section: Transport Imagesmentioning
confidence: 99%
“…Yes 84 422 No 93 524 Table 6 shows that even though during onshore wind conditions with wind speeds above 7 m/s, still 55% of the time transport was not observed. This can be related to water level variation which influences the groundwater level and therefore, the moisture content of the surface [52][53][54][55]. Figure 16 presents the cumulative distribution of water levels and wind speeds for the cases presented in Table 6.…”
Section: Transport Imagesmentioning
confidence: 99%
“…Key requirements for the development of coastal dunes are the availability of sediment, space for dune growth, suitable climate conditions (e.g. wind, waves, vegetation, and rain) and time for its development (Hesp, 1983(Hesp, , 2002Bochev-van der Burgh et al, 2009;Bauer et al, 2009;Bochev-van der Burgh et al, 2011;Keijsers et al, 2015;van Puijenbroek et al, 2017;Galiforni-Silva et al, 2018, 2019.…”
Section: Introductionmentioning
confidence: 99%
“…Although the elevation stability of most of the supra-tidal zone of the sand flat, together with no growth trend related to the depositional ridge, hints at such possibility, the main process that might lead to such limitation of the zone to act as a sediment source remains unclear. Silva et al (2018) shows that spatial variation in groundwater depth along the sand flat induces variations in sediment supply to the dunes, which may lead to an overall limitation of the sand flat to act as a source in the long-term. Hoonhout and de Vries (2017) suggested that in a mega-nourishment setting, wind transport would lead to a sorting process of the sediments at the beach surface that, within a certain period of time, would induce an armouring effect that could reduce the potential of the sediment surface to act as a sediment source.…”
mentioning
confidence: 99%